2020
DOI: 10.1136/emermed-2020-209891
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and usefulness of rapid 2-channel-EEG-monitoring (point-of-care EEG) for acute CNS disorders in the paediatric emergency department: an observational study

Abstract: IntroductionThe aim of this study was to determine the feasibility and clinical utility of point-of-care electroencephalogram (pocEEG) in the paediatric emergency department (ED) for children presenting with acute non-traumatic central nervous system (CNS) disorders.MethodsRetrospective observational study of prospectively collected data in paediatric patients (0–16 years) with acute non-traumatic CNS-disorders presenting between April 2014 and February 2017 to a single paediatric ED in Switzerland.The 2-chann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 18 publications
2
14
0
Order By: Relevance
“…36 In addition, studies demonstrated the feasibility of EEG with reduced number of electrodes for the detection of NCSE in emergency outpatient adults and pediatric patients with altered consciousness. 9,37 Therefore, the reported reliability of sEEG in previous studies lend support for its validity in the current study population.…”
Section: Reliability Of Seegsupporting
confidence: 73%
See 1 more Smart Citation
“…36 In addition, studies demonstrated the feasibility of EEG with reduced number of electrodes for the detection of NCSE in emergency outpatient adults and pediatric patients with altered consciousness. 9,37 Therefore, the reported reliability of sEEG in previous studies lend support for its validity in the current study population.…”
Section: Reliability Of Seegsupporting
confidence: 73%
“…Few studies have examined the validity of sEEG in pediatric patients; however, a study on neonatal patients reported that the sensitivity and sensitivity of single-pole induced EEG with reduced electrodes for detecting brain-wave abnormalities were 94% and 78%, respectively, which were comparable with those of standard EEG 36 . In addition, studies demonstrated the feasibility of EEG with reduced number of electrodes for the detection of NCSE in emergency outpatient adults and pediatric patients with altered consciousness 9,37 . Therefore, the reported reliability of sEEG in previous studies lend support for its validity in the current study population.…”
Section: Discussionsupporting
confidence: 62%
“…When compared to 104.5 min using a conventional EEG, significant time savings were seen with the EEG cap, which has a median “time to cap” EEG recording of 22.5 min. In summary, as shown in the current studies, rapid diagnosis of NCSE or other diagnoses supported using EEG in the future can be made quicker by wearables [ 21 ].…”
Section: Time To Eegmentioning
confidence: 96%
“…Simma et al demonstrated that NCSE was identified in six out of 36 patients in a convenience sample, using a limited 2-electrode point-of-care EEG system applied by emergency nurses and interpreted by emergency physicians with the assistance of remote pediatric neurology consultants [ 21 ].…”
Section: Pediatric Emergency Eegmentioning
confidence: 99%
“…A simplified EEG performed at the bedside in the ED has been shown to complement clinical, laboratory, and imaging assessment and aid patient management [ 15 , 16 ]. A pocEEG has proven useful for evaluating altered mental status, detecting NCSE, and monitoring the treatment of ongoing SE [ 17 ]. In a retrospective pediatric cohort, 41/242 (17%) patients with altered mental status were diagnosed with non-convulsive seizures in pocEEG.…”
Section: Introductionmentioning
confidence: 99%